Balancing Performing and Teaching Roles: The Voice of Classical Singers - Haldane, Christina Raphaëlle (Frontiers in Psychology, 2018)
How do classical singers combine performing and teaching, two highly challenging and consuming careers? The life of a performer combines reward with intense challenging commitment. Furthermore, for the classical vocalist whose body is the instrument, maintaining good health is a priority. Teachers of singing have demanding roles, with the responsibility of guiding their students’ vocal technique, in addition to providing inspiration, emotional support and career guidance. Moreover, their work can be taxing on their voices. There is research pertaining to musicians who balance teaching and performing, however the literature reviewed did not present a study which focused solely on classical singers who also teach, whose operatic engagements can be lengthy and travel-orientated. This gap in the literature provided an opportunity to contribute further to the field and examine the relationship between successfully balancing a performance and teaching career for classical vocalists. My aim was to explore: 1) how classical vocalists with extensive performance schedules maintain a commitment to their teaching studio; and 2) how teachers of singing who manage large private studios, and/or teach at high-level music institutions, balance performance careers with their responsibilities to their students. A phenomenological approach was selected for my exploratory study, using a qualitative method to devise an interview guide and analyze data. The procedure used for selecting the sample group was to invite participants representing a range of professional involvement in both teaching and performing. Diversity with regards to gender, base location and experience was also considered. Participants mainly responded via e-mail interviews. They were invited to discuss the following themes: balancing performing obligations with commitments to students, benefits of performing on pedagogy, and maintaining vocal health. Overall, participants felt that their performance experience was essential to their work in the teaching studio, with performing seen as a source of learning to be transmitted to students. On the other hand, for some, teaching was also seen as a source of learning, enhancing performances. Although demanding, the benefits of maintaining and enjoying both a teaching role and an active performing life were affirmed by participants. Attempting to balance both roles becomes a constant quest.